Pemenuhan Hak Memperoleh Pekerjaan Bagi Penyandang Disabilitas Berdasarkan Undang-Undang Nomor 8 Tahun 2016 Tentang Penyandang Disabilitas - Delfina Gusman Gusman; Didi Nazmi Nazmi; Yunita Syofyan Syofyan (Riau Law Journal, 2022)
Human Rights (HAM) is a gift from God to his creatur human rights should not be kept away or separated from the personal existence of the individual or human being. Protection of persons with disabilities has 22 (twenty two) rights. This arrangement is regulated through Article 5 regarding an elaboration of the rights that will be received for individuals with disabilities in carrying out the nature of their lives until they die. Persons with disabilities also have the right to work and get rewarded for their hard work and of course it has been regulated through the written constitution of the Republic of Indonesia. Without realizing it in almost all areas of life, people with disabilities are still discriminated against. There is even an assumption from some people that the affairs of people with disabilities are solely the business of the Social Service or the Ministry of Social Affairs. The research method uses normative juridical (empirical legal research) with a statutory approach (statue approach) and an analytical approach (conceptual approach). First, The fulfillment of employment opportunities for people with disabilities shows that there is still a shortage due to the need for job providers, the quality of people with disabilities, and their still being selective in every job field on a micro basis. The city of Padang related to employment rights for persons with disabilities continues to strive to fulfill their work rights. Third, In the legal construction of regulating employment rights for Persons with Disabilities, there must be a balance towards optimizing work through personnel from persons with disabilities. So that the fulfillment of the law both das sollen and das sein is accommodated appropriately